2014
DOI: 10.1002/ajmg.a.36374
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Profile in RASopathies

Abstract: Here, we describe neurobehavioral features in patients with RASopathies (i.e., Noonan syndrome, LEOPARD syndrome, Costello syndrome, and cardiofaciocutaneous syndrome), developmental disorders caused by mutations in genes coding transducers participating in the RAS-MAPK signaling cascade. Parents of 70 individuals with a RASopathy were asked to fill out the following questionnaires: Child Behavior Checklist (CBCL), Social Communication Questionnaire version lifetime (SCQ-L), and Modified Checklist for Autism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 42 publications
(44 reference statements)
7
96
0
Order By: Relevance
“…In contrast to these findings, studies using standardized symptoms checklists have not found a significant difference in anxiety and depression symptoms in adults with NS compared with unaffected adults (Wingbermühle et al 2012a). Similarly, most studies have found no differences in parent-reported levels of depression/anxiety symptoms between children with NS compared with typically developing children (Pierpont et al 2015;Wood et al 1995;van der Burgt et al 1999), although Alfieri et al (2014) reported a 32 % rate of clinically elevated depression/anxiety symptoms in their sample of children with NS. In terms of self-concept, Lee et al (2005) administered the Piers-Harris Children's SelfConcept Scale (Piers and Harris 1989) to assess self-esteem in 30 children with NS.…”
Section: Psychopathology/mental Healthmentioning
confidence: 84%
See 4 more Smart Citations
“…In contrast to these findings, studies using standardized symptoms checklists have not found a significant difference in anxiety and depression symptoms in adults with NS compared with unaffected adults (Wingbermühle et al 2012a). Similarly, most studies have found no differences in parent-reported levels of depression/anxiety symptoms between children with NS compared with typically developing children (Pierpont et al 2015;Wood et al 1995;van der Burgt et al 1999), although Alfieri et al (2014) reported a 32 % rate of clinically elevated depression/anxiety symptoms in their sample of children with NS. In terms of self-concept, Lee et al (2005) administered the Piers-Harris Children's SelfConcept Scale (Piers and Harris 1989) to assess self-esteem in 30 children with NS.…”
Section: Psychopathology/mental Healthmentioning
confidence: 84%
“…Earlier studies using parent report measures such as the Child Behavior Checklist have noted children with NS showed greater difficulties related to attention and hyperactivity relative to comparison groups or normative data, although statistically significant differences were not always reported (van der Burgt et al 1999;Wood et al 1995;D. A. Lee et al 2005;Sarimski 2000;Alfieri et al 2014). More recently, Pierpont et al (2015) compared a cohort of children with NS with a sibling comparison group on a range of measures examining attention skills.…”
Section: Attention and Executive Functioningmentioning
confidence: 91%
See 3 more Smart Citations